Dynamics and enzymatic degradation of exopolymer particles under increasing concentrations of silver ions and nanoparticles during a marine mesocosm experiment - Scheidemann, Lindsay; Pontiller, Benjamin; Manna, Vincenzo; Cisternas-Novoa, Carolina; Celussi, Mauro; Tsiola, Anastasia; Pitta, Paraskevi; Magiopoulos, Iordanis; Engel, Anja (Frontiers in Marine Science, 2022)
Pollution of the marine environment is an emerging threat. Nowadays, engineered nanoparticles (<100 nm) such as zinc, copper and silver are widely used as antimicrobial agents, therefore often present in daily-life products. Consequently, the demand and production of nanoparticles are expected to increase. Here, we specifically focus on silver nanoparticles (AgNP). Once released into the environment, AgNPs pose an obvious ecotoxicological risk, potentially affecting ecosystem structure and functioning. For instance, phytoplankton-derived exudates, rich in acidic polysaccharides and amino acids, can abiotically aggregate into microgels such as transparent exopolymer particles (TEP) and Coomassie stainable particles (CSP). Hence, microgels can bridge dissolved and particulate size fractions and facilitate aggregate formation with organic and mineral particles. Both physical and chemical properties make TEP and CSP attractive nutrient hotspots for heterotrophic bacterioplankton. Bacteria, in turn, utilize extracellular enzymes to access these carbon and nitrogen pools. However, knowledge about the mechanisms by which AgNPs might interact with and affect the biogeochemical cycling of TEP and CSP is still insufficient. Therefore, we conducted a mesocosm experiment in the Eastern Mediterranean Sea and investigated the effects of environmentally relevant concentrations of silver ions (Ag+) and AgNP on the properties of TEP and CSP (i.e., area and abundance) along with enzymatic activity measurements. Our results showed that cyanobacteria were likely the primary source of CSP in the ultra-oligotrophic Mediterranean Sea. Also, CSP contributed more to the microgel pool than TEP, as indicated by a strong relationship between CSP and heterotrophic microbial dynamics. While silver (i.e., Ag+ or AgNP) had overall only marginal effects, both species affected the relationships between cell-specific LAPase activity and CSP and cell-specific APase activity and phosphate levels. Thus, Ag+ and AgNP have the potential to regulate microgel dynamics. However, future studies are needed to derive a robust understanding of the effects of silver pollution on the coupling of microgel formation and degradation and the follow-on effect on biogeochemical cycles.